1879 Wyo. Terr. Sess. Laws 97, ch. 43, § 1. - (:unkn) unknown (My University, 1879)
It shall be unlawful for any person in this territory to fire any rifle, revolver, or other fire arm of any description whatever, from any window, door, or other part of any railroad car or train, engine or tender, or along the line of railroad during the passing of any train or engine, or when any person is passing in the vicinity of the person having such fire arm, and any person so offending, shall, on conviction, be fined in a sum not exceeding twenty ($20.00) dollars, and for a second offense, confined in the county jail for a term not exceeding sixty (60) days.
Keywords: DISCHARGE